2012
DOI: 10.4081/ijas.2012.e39
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of growth performance, meat quality and haematological parameters of Fayoumi, Rhode Island Red and their reciprocal crossbred chickens

Abstract: A total of 2001 unsexed day-old-chicks of each Fayoumi, Rhode Island Red (RIR), RIR × Fayoumi (RIFI) and Fayoumi × RIR (FIRI) were obtained from hatchery of Poultry Research Institute, Rawalpindi. The birds were maintained on deep litter system for a period of 20 weeks. The results revealed that the average day old weight was highest in RIR and FIRI, intermediate in RIFI and lowest in Fayoumi chickens. The RIR breed consumed more feed and gained maximum (P<0.05) weight gain than those of Fayoumi and crossbred … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 11 publications
(13 reference statements)
1
15
0
Order By: Relevance
“…Growth performance of EM, WB, and CB increased under identical diet and feeding conditions are presented in Table 2 . The ADG and gain:feed were the highest in CB, intermediate in WB, and the lowest in EM ( p <0.05), consistent with previous reports ( Khawaja et al ., 2012 ; Lichovnikova et al ., 2009 ; Lonergan et al ., 2003 ). Huque et al .…”
Section: Resultssupporting
confidence: 92%
“…Growth performance of EM, WB, and CB increased under identical diet and feeding conditions are presented in Table 2 . The ADG and gain:feed were the highest in CB, intermediate in WB, and the lowest in EM ( p <0.05), consistent with previous reports ( Khawaja et al ., 2012 ; Lichovnikova et al ., 2009 ; Lonergan et al ., 2003 ). Huque et al .…”
Section: Resultssupporting
confidence: 92%
“…Our previous work on the growth pattern in chickens of reciprocal crossing between RIR and Fayoumi breeds has been published recently (Khawaja et al 2012). The results showed that crossbred chickens of FIRI (Fayoumi male)RIR female) showed better performance in all traits than crossbred chickens of RIFI (RIR male )Fayoumi female).…”
Section: Introductionmentioning
confidence: 98%
“…Previous studies have reported that White Leghorns crossed with Bedouin fowl (a breed that is adapted to desert conditions and can withstand both hot summers and cold winters) can produce chickens that are similarly well adapted [ 6 ]. Other studies report that Fayoumi, a heat tolerant breed, can be crossed with other breeds to produce crossbreds with improved adaptation and fitness traits [ 11 ]. Thus, crossing BS with a commercial line to produce cold tolerant high performance laying chickens might be feasible.…”
Section: Introductionmentioning
confidence: 99%